Selective Colorimetric Detection of Mercury(II) using Silver Nanoparticles-Chitosan - Monica Avissa; Mohammad Alauhdin (Universitas Jenderal Soedirman, 2022)
Contamination of the environment by hazardous metal ions has been a major environmental issue for the past several decades. Among several hazardous metals, mercury ion (Hg(II)) is of particular concern as its compounds are extremely toxic. Hence, developing detection methods for traces of Hg(II) ions in aquatic systems is critical for mercury pollution mitigation. One method that can be used to monitor Hg(II) in aquatic systems is colorimetry-based method which is simple, rapid, and low-cost, yet selective and sensitive. The method can be conducted by applying the Localized Surface Plasmon Resonance phenomenon of metal nanoparticles, such as silver nanoparticles. There are non-Hg(II) ions in the aquatic environment that can interfere the measurements. Thus, a selective method is needed to obtain a valid measurement result. Here, we introduced silver nanoparticles-chitosan (AgNPs-Ch) synthesized by chemical reduction as a selective probe of Hg(II) in an aqueous solution. The AgNPs-Ch was synthesized from silver nitrate at 80°C using trisodium citrate and chitosan as reducing agent and stabilizer, respectively. The synthesized nanoparticles were spherical with an average size below 15.0 nm. Moreover, the AgNPs-Ch was selective for Hg(II) with a linearity of 0.9556 in the concentration range of 1 - 5 ppm and was able to detect the ion down to 1.33 ppm.